Memories and Mechanisms of Resistance to the Atlantic slave trade: the Ekang Saga in West Central Africa's epic tale the Mvet - (:unkn) unknown (My University, 2018)
The exploration of African oral literature has cast new light on the history of the Atlantic slave trade. Working on diverse regions and from various sources, scholars have used folk materials for a new understanding of slave trade mechanisms. Building on the Mvet epic tale of West Central Africa, the present paper investigates the techniques of encryption of slave trade-related memories. It looks into the philosophical and moral tenets of the Mvet to argue that the tale was not only a strategy of resistance to the alienating ethics of Western capitalism, it also reads as a humanist discourse through which the Fang-Beti-Bulu people asserted their agency against the commodification of the black body. This paradigm reverberates across postcolonial societies of Gabon, Cameroon and Equatorial Guinea with the appropriation of the Mvet art by a new generation of artists who have recalibrated the ancient epic to serve as instrument of resistance to Western cultural hegemony, and as a regenerative site for postcolonial identities. With its legendary superheroes and sophisticated weaponry, the mythic territory of the Mvet anticipates the Afro-futuristic universe of Wakanda in the American Marvel film Black Panther.
Keywords: African Research